2017
DOI: 10.1111/ajt.14278
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective and Antioxidant Effects of Steen Solution on Human Lung Spheroids and Human Endothelial Cells

Abstract: Respiratory diseases represent a major healthcare burden worldwide. Lung transplantation (LTx) is the "gold standard" for end-stage patients, strongly limited by shortage of available/suitable donor lungs. Normothermic ex vivo lung perfusion (EVLP) has significantly increased the number of lungs suitable for transplantation. Steen solution is used for EVLP, but the mechanisms involved in its beneficial properties remain to be clarified. We investigated the effects of Steen solution in an in vitro protocol of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…21 Steen as perfusate had previously been tested in pig liver transplant studies and has been extensively used in normothermic ex vivo lung perfusion. 22,23 Steen is extensively used in clinical trials for ex vivo lung preservation, demonstrating promising results, 2426 as well as in the first North American human trial of NEsLP. 3 Gelofusine in contrast has been used for the majority of NEsLP in European clinical studies.…”
mentioning
confidence: 99%
“…21 Steen as perfusate had previously been tested in pig liver transplant studies and has been extensively used in normothermic ex vivo lung perfusion. 22,23 Steen is extensively used in clinical trials for ex vivo lung preservation, demonstrating promising results, 2426 as well as in the first North American human trial of NEsLP. 3 Gelofusine in contrast has been used for the majority of NEsLP in European clinical studies.…”
mentioning
confidence: 99%
“…Pre-clinical studies have reflected anti-oxidant properties of Steen solution in EVLP. The solution was able to particularly reduce NADPH oxidase 2 isoform activation, promoting preservation of the lung epithelial cells [145]. Furthermore, 2% sevoflurane administered intravascularly during EVLP has been shown to reduce oxidative stress and the inflammatory response [146].…”
Section: Evlp and Cold Storage: Effects On Oxidative Stressmentioning
confidence: 99%
“…In fact, OXS strongly contributes to tissue damage during EVLP. It has been shown that inhibition of NOX2 activity during thermic stress and starvation (mimicking EVLP conditions) can reduce ROS production, thus being protective for lung epithelial cells [63,64]. Finally, specific interference of cigarette smoke with Wnt/β-catenin signaling has been described in human fibroblasts, impairing their capacity to support spheroid growth of lung epithelial cells, which can be considered in this case as a stemness assay linked to the activation of a repair mechanism [65].…”
Section: Modelling Lung Diseases In 3d With Organoidsmentioning
confidence: 99%